Development of Android-Based Digital Pocketbook Learning Media in Pancasila and Citizenship Education Subjects For Class VIII SMP - Iskandar, M Yakub; Nugraha, Ridho Aprilia; Halimahturrafiah, Nur; Amarullah, Taufik Abdul Hasan; Putra, Dino Adi (JERIT: Journal of Educational Research and Innovation Technology, 2024)
This research aims to develop an Android-based digital pocketbook application learning media for the Pancasila Citizenship Education subject: determine the feasibility of an Android-based digital pocketbook application learning media based on the assessment of media experts, material experts, and learning language experts as well as learning media users. This research is development research (Research and Development) with the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model. Media validation was carried out by Material Experts, Media Experts and Language Experts for Pancasila Citizenship Education. The media developed was tested on 22 respondents. The results of the research show that the level of feasibility of the Articulate Storyline application learning media is based on assessments: 1) Material Experts obtained an assessment score of 82.86%, including in the very feasible category. 2) Media Experts obtained an assessment score of 82%, which is in the very worthy category. 3) Linguist experts obtained an assessment score of 85%, which is in the very appropriate category. 4) The respondent's assessment obtained an assessment score of 98%, including in the Very Decent category. The research results show that the Android-based Digital Pocketbook Learning Media developed is very suitable for use as a learning media for Pancasila Citizenship Education.